2020
DOI: 10.1021/acs.orglett.0c00618
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Direct C–H Amidation Producing Multicolor Fluorescent Molecules Emitting Blue-to-Red Light and White Light

Abstract: We report a powerful strategy, iridium-catalyzed direct C–H amidation (DCA) for synthesizing various fluorescent sulfonamides that emit light over the entire visible spectrum with excellent efficiency (up to 99% yields). By controlling electronic characters of the resulting sulfonamides, a wide range of blue-to-red emissions was predictably obtained via an excited-state intramolecular proton-transfer process. Furthermore, we even succeeded in a white-light generation, highlighting that this DCA is an excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Large Stokes shifts (Δλ = 140–179 nm for P2 , P4 , P9 , and P13 ) were observed (Figure S12). Similar photophysical properties were observed for the polysulfonamides and sulfonamides by Choi et al ,, They assume that the emission was induced by an excited-state intramolecular proton-transfer process. Herein, as P4 an example, a proton on the sulfonamide moiety (hydrogen-bond donor) may migrate to the neighboring carbonyl group (hydrogen-bond acceptor) upon photoexcitation.…”
Section: Resultssupporting
confidence: 79%
“…Large Stokes shifts (Δλ = 140–179 nm for P2 , P4 , P9 , and P13 ) were observed (Figure S12). Similar photophysical properties were observed for the polysulfonamides and sulfonamides by Choi et al ,, They assume that the emission was induced by an excited-state intramolecular proton-transfer process. Herein, as P4 an example, a proton on the sulfonamide moiety (hydrogen-bond donor) may migrate to the neighboring carbonyl group (hydrogen-bond acceptor) upon photoexcitation.…”
Section: Resultssupporting
confidence: 79%
“…and extending the π-conjugated framework, various types of fluorophores that emit light covering the full-colour range from blue to the NIR region have been achieved[24][25][26]. To achieve full-colour solvatochromic photoluminescence, blue, green, and red colour emissions (light's three primary colours) are essential.…”
mentioning
confidence: 99%
“…Notably, these polymerization conditions were later applied to a new set of small molecule substrates, focusing on C–H amidation of aryl amides by tosyl azide. 87 With the use of the insights from the polymer synthesis, the materials prepared contained various substitution patterns to provide a collection of multicolor fluorophores. These three methods, starting from a small molecule method, then a novel polymerization, and last a new small molecule approach, demonstrate the synergistic discovery accessible between small molecule methodology and new methods of polycondensation.…”
Section: Emerging Polymerization Methodologies Beyond Darpmentioning
confidence: 99%
“…During characterization of these materials, it was observed that these polysulfonamides were blue-light emitters with high quantum yields, arising from hydrogen bonds between the sulfonamide and adjacent carbonyl. Notably, these polymerization conditions were later applied to a new set of small molecule substrates, focusing on C–H amidation of aryl amides by tosyl azide . With the use of the insights from the polymer synthesis, the materials prepared contained various substitution patterns to provide a collection of multicolor fluorophores.…”
Section: Emerging Polymerization Methodologies Beyond Darpmentioning
confidence: 99%